Avaliação do precoating e dos meios filtrantes para filtro de mangas do processo de despoeiramento secundário da aciaria - Andrade, Bárbara Karolinne Silva Araújo (Universidade Federal de São Carlos, 2019)
Constant exposure to high concentrations of particulate matter present in the air has increased the number of cases of cardiorespiratory disease and death. Since then, has been a need for the development and improvement of gas cleaning processes and equipments. Among these, we have the bag filter which is one of the most used in the industries due to the high efficiency, above 99.9%. Its filtration efficiency is directly related to the type of filter medium. The filter media with fiber coating with a thin PTFE membrane has a good industrial application, guaranteeing high collecting and cleaning efficiencies, but it is high cost and less used than polyester. An alternative pre-treatment for increasing collection efficiency in cheaper filter media is the precoating. This prevents clogging of the filter media by coating the bags with a particulate material to prevent the penetration of submicron particles in the first cycle. It is responsible for the clogging, which is the initial formation of the cake, ensuring surface filtration. The choice of the precoating powder and the filter medium to be used is of great influence to the efficiency of the filtration process. Thus, this work aims to determine the precoating powder and the most suitable filter media in the filtration of material from the secondary dusting of the steelworks of a steel mill. For this purpose, the characterization of the particulates was initially carried out. Next, the filter media (polyesters, PTFE membrane polyester and PTFE encapsulated polyesters) were characterized to obtain fiber diameter, porosity and permeability. Thus, maximum precoating load loss tests were performed and the precoating mass variation required to achieve the lowest emission of particulate material was evaluated. The collection efficiencies for micro and nanoparticles were also evaluated for virgin filter media. Thirty cycles of filtration with and without precoating in polyester were carried out up to the maximum pressure loss of 100 mmH2O with pulsed air jet cleaning to verify the need for precoating or not. It was found that the precoating increased the shelf life of the polyester and allowed the reduction of the penetration of particles in the filter medium. The efficiency of the dirty sleeves of three different compartments was evaluated and it was concluded that efficiency decreased compared to a virgin sleeve.
Evaluation of precoating and filtrating media for sleeve filters of the secondary disposal process of the association
Keywords: Filtro de mangas; Meio filtrante; Filtração ar-sólido; Jato pulsante de ar; Baghouse; Filter media; Air-solid filtration; Pulse-jet; Precoating; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA